Penyebab dan Upaya yang Dilakukan Para Pemerintah Dunia Saat Krisis Global 2008 - Herawati, Hasmiah; Gustan, Mukarramah (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2020)
In this globalization era, economic integration is increasingly in line with information technology. In a very short period of time, the financial crisis that occurred in the United States quickly spread to other countries so that it developed into a problem that was quite serious which had the effect of economic finance. This 2008 crisis is a very bad global financial crisis in the past 80 years. The crisis that was initially experienced due to subprime mortgages in the United States turned out to affect the international world. Therefore, the country's leaders strive to minimize the crisis by holding a meeting attended by the G-20. The G-20 is a major economic group in the world.